FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT WAKAF PRODUKTIF DALAM PEMBERDAYAAN PENYANDANG DISABILITAS - Rani, Lina Nugraha; Sa'adah, Fetta Nabilatus; Hidayah, Binti Khusnul (Airlangga Journal of Innovation Management, 2025)
The introduction or problem This study aims to analyze the factors influencing the intention to give productive waqf to support the lives of people with disabilities. This research employs a quantitative approach using primary data collected through the distribution of online questionnaires to 60 respondents. The obtained data were then analyzed using path analysis with SPSS 27 to determine the relationships between the variables. The findings of this study indicate that the information media variable has a significant positive influence on the intention to give productive waqf to empower persons with disabilities. This suggests that the more information and awareness people have about productive waqf and its benefits, the higher their participation in waqf donations. Meanwhile, the variables of public perception, religiosity, and income were found to have no significant influence on the intention to engage in productive waqf. The results of this study can serve as a reference for the government and the Indonesian Waqf Board (BWI) in developing more effective strategies to increase public participation in productive waqf. Disseminating information through online media such as social media and offline media such as brochures can be a strategic effort to raise public awareness. Future research is recommended to use qualitative methods by conducting interviews with economic and waqf experts, as well as persons with disabilities, to gain deeper insights into their perceptions of this empowerment program.